Chinese Temples and Buddhism Unite In Harmony - Ardian Cangianto (Jounal Nyanadassana, 2022)
Relationship history between China and Indonesia Archipelago has been recorded since 1st century and followed by Chinese community to migrate to the archipelago at that time. The migration also brought their beliefs and culture to enrich archipelago culture. Chinese people and their temples role in developing Buddhism were not discussed in detail, even, there were many misunderstandings between temples and Buddhism institutions. Further, to overcome this problem, we must understand how Chinese belief system and temple role in developing Buddhism in 18th to 21st centuries. Chinese temple's track record is dominant in Buddhism development. Benqing monk's record who traveled from one temple to another in providing services for people in temples or Mahayana Buddhist was possible to be traced. In addition, role of Dizang Yuan in Jakarta to educate the "flower monks" as prayers. Even the role of spreading Buddhism through symbols could be seen in various temples. Absolutely, this role requires better establishment and deeper understanding of Chinese people beliefs and temple function as an effort to build harmony. Furthermore, Chinese temples division and belief systems with "Three Teachings" are required to be studied deeper. So, we can all understand that the core is "harmony”